A Complex Circuit Tolerance Analysis Method Based on Affine Analysis. Issue 5 (January 2021) - Huo, Xiangli; Ma, Cong
Abstract: In this paper, the selection of tolerance analysis objects and the uncertainty in the process of tolerance analysis for complex circuit systems are studied. A relatively perfect principle for determining the key circuits of tolerance analysis is formed. And considering the linear and nonlinear problems of circuits, based on the affine analysis method, a tolerance analysis method considering the influence of random factors is studied. Then the oretical basis and implement steps of the mfethod is given finally, and the application of the typical circuit in a product circuit system is verified.